Enhancing websites an educational technology based-model - Monzon, Cynthia P. (2007)
The World Wide Web has become a widely used tool to find information and to conduct business. This study attempted to evaluate the National Housing Authority (NHA) Web site. There are three basic components which affect the user's perception and evaluation of the Web site namely content, visual design, and navigation design. A list of criteria was developed to evaluate the three components. Personal interviews with three Web designers were also conducted. The evaluation revealed that employees perceived that information on the Web site lack objectivity, accuracy, currency, coverage, and authority, while students and Web designers perceived the information accurate, complete, updated, informative, labeled, interesting, and had appropriate level of content, vocabulary for intended audience. The study recommended an educational technology based model for designing, developing, enhancing, and evaluating Web sites.